Fluid mechanics of aortic valve incompetence in the dilated left ventricle - Vu, Vi; May-Newman, Karen (Frontiers in Medical Engineering, 2024)
Aortic insufficiency (AI) occurs when the aortic valve fails to close completely, allowing backward blood flow into the left ventricle (LV). The progression of AI can lead to ventricular dysfunction and congestive heart failure, setting off a self-perpetuating cycle that worsens these conditions. This study employed models of repeatable and reversible AI within a simulated circulatory loop to analyze vortex dynamics, AI parameters, and gain insights into the efficiency of ventricular washout.A transparent silicone model of an LV with an ejection fraction of 17% served as the baseline, simulating a condition without AI. Mild, moderate, and severe AI were induced using 3D-printed stents, obstructing the complete closure of the aortic valve while allowing unimpeded forward blood flow. Midplane velocity fields were analyzed to compute AI and vortex properties, energy dissipation rate, blood residence time, and shear activation potential.With increasing AI severity, the regurgitant jet expanded, impeding the development and trajectory of mitral inflow. The inefficiency in fluid transport became apparent through a declining ratio of total kinetic energy rate to energy dissipation rate and an increasing residence time. Impaired ventricular washout resulted in the accumulation of fluid with elevated shear activation potential in the LV. These findings suggested that AI progressively induces abnormal intraventricular flow, heightening the thromboembolic risk in heart failure patients. The study also advocates for the potential application of mock circulatory system to explore the effects of various AI configurations, especially when combined with other cardiac implants like artificial heart valve or left ventricular assist device.